Disaster Geography Learning Media Indonesian Secondary Schools: Identification, Challenges, and Innovations - Mohamad Tusam; Lili Somantri; Iwan Setiawan (Indonesian Journal of Educational Research and Review)
Geography education plays a strategic role in fostering environmental awareness and enhancing disaster preparedness. However, the effectiveness of disaster-related learning in secondary schools continues to face various challenges, particularly in the use of innovative instructional media. This study aims to analyze trends, challenges, and innovations in the use of geography learning media for disaster education during the period 2014–2024. A systematic literature review was conducted using articles obtained from the Scopus and Semantic Scholar databases, assisted by the Publish or Perish software. Inclusion criteria consisted of peer-reviewed articles written in Indonesian or English that were relevant to the topic. Article selection and quality assessment were performed using the Critical Appraisal Skills Programme (CASP), and data were analyzed thematically. The review findings indicate a significant increase in the use of digital learning media such as Google Earth, Augmented Reality, Moodle, Story Maps, and gamification, all of which have been shown to enhance student engagement and comprehension of disaster concepts. Most studies reported improvements in both cognitive and affective learning outcomes following the implementation of these innovative tools. Nevertheless, their practical application remains limited due to inadequate teacher training, technological infrastructure constraints, and suboptimal curriculum integration. Accordingly, this study recommends a systemic approach to developing and implementing learning media, which includes improving teachers' pedagogical and digital competencies, strengthening policy support, and ensuring adequate technological infrastructure in schools.